2016
DOI: 10.1002/jmv.24661
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, seasonality, and clinical characteristics of respiratory viruses in children with respiratory tract infections in Eastern India (Bhubaneswar, Odisha)

Abstract: Acute respiratory tract infections (ARTIs) are a leading cause of morbidity and mortality in young children in low and middle income countries. To analyse the overall burden of respiratory viruses responsible for ARTIs in paediatrics population in eastern India, this study was performed. Clinical information, demographic information and nasal/oral swabs were collected from 332 paediatric patients (aged from 1 month to 12 years old) with the symptoms of ARTI, enrolled from the outpatient department from Nov 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
6
21
0
Order By: Relevance
“…Of 13 patients who died, 10 were because of coinfection. Similar findings have been observed by authors from India and abroad [20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Of 13 patients who died, 10 were because of coinfection. Similar findings have been observed by authors from India and abroad [20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…In the study by Yeolekar et al, RSV was the most frequently detected virus (26%) from hospitalised children presenting as ALRI followed by IFV (5.4%), PIV (2.07%), and ADV (0.8%) [19]. Panda et al recently found RV as the most frequently detected pathogen (24.7%) followed by RSV (4.22%), PIV (2.11%), and hMPV (2.11%) in children with ARI from Eastern India [20]. In the present study, we found RV as the second most important agent to RSV causing ARI in young infants and children.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…ARTI prevalence in children varies by geographic area, season, and year (Goktas and Sirin, 2016;Moura et al, 2009;Panda et al, 2017). Recent Italian data are limited, apart from those relating to influenza (Pariani et al, 2015;Trucchi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Coinfections with different multiple viruses were reported in 15% to 61% of patients. [6][7][8][9]. Molecular techniques such as multiplex polymerase chain reaction (PCR) are widely used for the detection and identification of respiratory viruses [10][11][12] and are helpful in the management and treatment 2 BioMed Research International of respiratory infections [13].…”
Section: Introductionmentioning
confidence: 99%